Contemporary imaging methods for the follow-up after endovascular abdominal aneurysm repair: a review - Wojciech Kazimierczak; Zbigniew Serafin; Natalia Kazimierczak; Przemysław Ratajczak; Waldemar Leszczyński; Łukasz Bryl; Adam Lemanowicz (Videosurgery and Other Miniinvasive Techniques)
Abdominal aortic aneurysm (AAA) is defined as a localized enlargement of the aortic cross-section where the diameter is greater than 3 cm or more than 50% larger than the diameter in a normal segment. The most important complication of AAA is rupture, which, if untreated, results in mortality rates of up to 90%. Conventional open surgical repair is associated with significant 30-day mortality. Endovascular aneurysm repair (EVAR) is a significantly less invasive procedure; it is related to a lower early mortality rate and a lower number of perioperative complications. Although EVAR is a minimally invasive technique, lifelong follow-up imaging is necessary due to possible late complications including endoleak, recurrent aneurysm formation, graft infection, migration, kinking and thrombosis. The total rate of complications after EVAR is estimated at approximately 30%, and the rate of complications that require intervention is 2–3%. Early detection and progression analysis of such situations is crucial for proper intervention.